A Comprehensive Overview of Perimidines: Synthesis, Chemical Transformations, and Applications - Harry, Nissy A.; Ujwaldev, Sankuviruthiyil M.; Aneeja, Thaipparambil; Anilkumar, Gopinathan (Current Organic Chemistry, 2021)
Perimidines are nitrogen-containing heterocyclic scaffolds with a wide range of biological and material properties. Several synthetic transformations on perimidines afford fused heterocycles. This review focuses on every aspect of perimidines, including different synthetic procedures, reactions and applications, and covers the literature published up to the year 2020, using more than 170 references.
Keywords: applications